Association between socioeconomic status and dispensing of higher-risk drug classes and polypharmacy in older community-based populations: a nationwide cohort study - Juliane Frydenlund; Nicole Cosgrave; David J. Williams; Frank Moriarty; Emma Wallace; Ciara Kirke; Kathleen Bennett; Caitriona Cahir (European Journal of Clinical Pharmacology, 2025)
Background Higher-risk medications are associated with increased risk of medication-related harm in older populations. Aim To investigate the association between socioeconomic status (SES) and the prescribing of higher-risk drug classes and polypharmacy in older community-dwelling adults. Methods This prospective, population-based cohort study used linked data from the Irish Longitudinal Study on Ageing (TILDA, 2018), the Health Service Executive-Primary Care Reimbursement Service (HSE-PCRS), and the General Medical Services (GMS) scheme over a 2-year follow-up. SES was measured by education, income, and private health insurance. Higher-risk drugs included antithrombotic agents, beta-blockers, calcium channel blockers, diuretics, renin–angiotensin–aldosterone system (RAAS) inhibitors, psychoanaleptics, and NSAIDs. Polypharmacy was categorised as 0–4, 5–9, and 10 + drug classes. Multivariable logistic and ordinal regression models adjusted for age, sex, and multimorbidity were used. Results The study included 1,401 individuals aged ≥ 70 years (median age 79; 43% male); 53% had ≥ 3 chronic conditions. 43% had primary/no education, 46% had below-median income, and 55% lacked private health insurance. Antithrombotics were the most prescribed higher-risk drug (38%), and 41% had 10 + different drug classes. Higher-risk prescribing and polypharmacy were more prevalent in those with lower SES. Participants with low SES were significantly more likely to be prescribed higher-risk drugs and experience polypharmacy. The greatest association was for psychoanaleptics: adjusted OR 1.97 [95% CI: 1.32;2.95] for primary/no formal education vs. third-level education, and 1.73 [95% CI: 1.30;2.30] for no vs. private health insurance. Conclusion SES-related disparities in higher-risk prescribing highlight the need for targeted interventions addressing social determinants of health in older populations.